Expanding Brain–Computer Interfaces for Controlling Epilepsy Networks: Novel Thalamic Responsive Neurostimulation in Refractory Epilepsy - Gummadavelli, Abhijeet; Zaveri, Hitten P.; Spencer, Dennis D.; Gerrard, Jason L. (Frontiers in Neuroscience, 2018)
Seizures have traditionally been considered hypersynchronous excitatory events and epilepsy has been separated into focal and generalized epilepsy based largely on the spatial distribution of brain regions involved at seizure onset. Epilepsy, however, is increasingly recognized as a complex network disorder that may be distributed and dynamic. Responsive neurostimulation is a recent technology to detect and stimulate cortical and subcortical brain structures and has particular significance in the clinical treatment of medically refractory epilepsy. Closed loop responsive neurostimulation represents an important step forward to understand and target nodes in the seizure network. Conceptually, the thalamus acts as a central network node to regulate input to the cortex; clinically, several thalamic nuclei are safe and feasible targets. We highlight the first reported use of responsive neurostimulation as a first generation brain-computer interface to detect and stimulate the centromedian intralaminar thalamic nucleus in a patient with broad bilateral cortical onset of seizures. While neuromodulatory techniques have made significant progress since the initial efforts of brain stimulation, there exists numerous avenues of future direction including multi-modal and multi-site targeting within wireless brain computer interface devices.